2018
DOI: 10.1038/s41598-018-25126-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the sodium–glucose cotransporter 2 inhibitor luseogliflozin on pancreatic beta cell mass in db/db mice of different ages

Abstract: To examine the effects of luseogliflozin, a sodium–glucose cotransporter 2 inhibitor, on pancreatic beta cell mass in db/db mice of different ages. db/db mice aged 6, 10, 14 and 24 weeks old were fed either standard chow (control group) or standard chow containing 0.01% luseogliflozin (luseo group). After 4 weeks, immunohistochemistry and gene expression tests were conducted. In 6-week-old db/db mice, immunohistochemistry revealed a significant increase in beta cell mass in the luseo group compared with the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 32 publications
6
33
0
Order By: Relevance
“…Recently, Takahashi et al . administered the SGLT2 inhibitor luseogliflozin to 6‐, 10‐, 14‐ and 24‐week‐old db / db mice for 4 weeks, and found that Mafa and Pdx1 expression levels were increased, and the increased proliferation and suppressed apoptosis of pancreatic β‐cells were more evident in mice that were administered the drug earlier.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Takahashi et al . administered the SGLT2 inhibitor luseogliflozin to 6‐, 10‐, 14‐ and 24‐week‐old db / db mice for 4 weeks, and found that Mafa and Pdx1 expression levels were increased, and the increased proliferation and suppressed apoptosis of pancreatic β‐cells were more evident in mice that were administered the drug earlier.…”
Section: Discussionmentioning
confidence: 99%
“…We can easily presume that the early start of treatment for diabetes provides organ protection and the duration of treatment definitely influences its effectiveness, so study participants can be divided into two groups whose durations are the same, but were started at different times, namely, "early administration" and "late administration." Recently, Takahashi et al 23 administered the SGLT2 inhibitor luseogliflozin to 6-, 10-, 14-and 24-week-old db/db mice for 4 weeks, and found that Mafa and Pdx1 expression levels were increased, and the increased proliferation and suppressed apoptosis of pancreatic b-cells were more evident in mice that were administered the drug earlier. These results support the present findings and are of great importance, because they showed that SGLT2 inhibitors protect pancreatic b-cells more effectively when administered at the early phase.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors can increase insulin secretion and beta-cell mass but cannot increase insulin sensitivity [ 28 30 ]. However, Xu el.…”
Section: Discussionmentioning
confidence: 99%
“…One week of treatment with SGLT2 inhibitors in diabetic mice increased expression levels of the glucagon‐like peptide‐1 receptor and key β‐cell factors, which are critical for β‐cell function . Additionally, SGLT2 inhibitor treatment enhanced β‐cell proliferation by reducing oxidative stress in the islet cells . Third, the additive effect could occur via the restoration of liver dysfunction by treatment with SGLT2 inhibitors .…”
Section: Discussionmentioning
confidence: 99%